Factors Affecting Fishermen's Income in Kaili Village, Bissappu District, Bantaeng Regency - Muh Fahri (Pustaka Digital Indonesia, 2022)
This study aims to determine the effect of technology, capital and work experience on the income of fishermen in Kaili Village, Bissappu district, Bantaeng Regency. The population and sample for this study were 67 fishermen in Kaili Village, Bissappu district, Bantaeng Regency. The data analysis technique used in this study is multiple linear regression analysis with the help of the SPSS 25 program. The results show that the technology has a positive but not significant effect on the income of fishermen, this can be seen in the results of data processing where the regression coefficient is 557537.223 with a significant value greater than 0.05 (0.145> 0.05) . Capital has a positive and significant effect on the income of fishermen, this can be seen in the data processing results where the regression coefficient is 1.456 with a significant value less than 0.05 (0.000 <0.05). And work experience has a positive but not significant effect on the income of fishermen in Kaili Village, Bissappu District, Bantaeng Regency, this can be seen in the data processing results where the regression coefficient is 71170.501 with a significantly higher value than 0.05 (0.082> 0.05).